Increasing home-time for patients with heart failure in Sweden 1992–2008. (25th November 2020) - Ekestubbe, S; Fu, M; Giang, K.W; Lindgren, M; Rosengren, A; Schioler, L; Schaufelberger, M
Abstract: Background: Heart failure (HF) reduces survival and is one of the most common causes of hospitalizations in the elderly, imposing a major economic burden on the health care system, with frequency of rehospitalizations often used in interventional and observational studies in patients with HF. Home-time is a novel end-point measuring time spent alive and out of hospital and is easier for both clinicians and patients to relate to. Given the advances in treatment of HF over the last decades we postulated that an increase in home-time would follow. Purpose: To investigate whether home-time for patients with HF has changed over the last decades in Sweden and if home-time differs between patients of working age and those retired, or between men and women. Methods: Patients aged 18–84 years with a first hospitalization for HF in Sweden between 1992 and 2008 were identified using the National Inpatient Register which was linked to the Swedish Cause of Death Register. Information on rehospitalizations and mortality was collected and followed over a time period of 4 years. The patients were divided into two age groups: (i) <65 years and (ii) >65 years. The cut off 65 years was chosen being the official age of retirement over the study period in Sweden. Results: A total of 324, 907 patients were included in this study, mean age 73.5 years (standard deviation 9.3). Only 15.6% were <65 and 45.1% were women. In total, average home-time was 70.1% of the total follow up time, 2.1% of time was spent in hospital while, during a mean of 27.9% of the 4 year-period, patients were no longer alive. A small increase in home-time was observed over the study period. The older age group spent 67.7% at home compared with 83% in the younger group. After taking differences in mortality into account, the difference in home-time was no longer significant, with 92.7 and 95.8% home-time for the older and younger age groups, respectively. Over the entire study period older men had less home-time compared with older women. Since 1998 the reverse was true in younger men and women, where younger men had more home-time than younger women. Home-time increased for all subgroups over the study period with the most pronounced increase for younger men (see figure 1). Conclusion: Home-time for patients in Sweden increased over the study period and the increase was more marked for younger patients, where men spent more time at home than women. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): The Swedish state (ALF), The Swedish Heart and Lung Foundation, Västra Götaland Region, The Göteborg Medical Society